AN ANALYSIS OF MERCHANT BEHAVIOUR ON ISLAMIC BUSINESS ETHICAL PERSPECTIVES DURING COVID-19 PANDEMIC - Robby Kharisma; Syarifah Ida Farida; Iskandar Zulkarnaen (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The goal of this study was to assess how traders behaved during the Covid-19 pandemic in terms of Islamic business ethics, using the Home Industry in Pamulang, South Tangerang as a case study. This is a qualitative method of research. The study will take place in Pamulang, South Tangerang, with a focus on the Home Industry. Observation, interview, and documentation procedures are used to collect data. Credibility, transferability, dependability, and confirmatory data are used to determine the data's validity. Reduction, data exposure, and conclusion drawing are all steps in qualitative data analysis. The findings revealed that, from an Islamic Business Ethics perspective, the behavior of Home Industry traders, particularly in the Pamulang district of South Tangerang, was in line with Islamic Business Ethics. This is also reinforced by South Tangerang's regional motto, Smart, Modern, and Religious, which encourages individuals to trade in ways that are consistent with Islamic principles.